Wittgenstein and Nietzsche
1 online resource
Keywords: "This volume brings together essays that explore the intersections between Nietzsche and Wittgenstein from various perspectives. While some chapters focus on the philological and biographical connections of Wittgenstein's reading of Nietzsche, others reflect on the ideas that are implicitly shared by the two thinkers. For Nietzsche and Wittgenstein, philosophy is inextricably connected to ethics and the arts and therefore takes a peculiar method that differs from the sciences. Nevertheless, their thinking strives for knowledge and truth by means of discursive text forms, however unconventional they may be. The first group of chapters contextualize explicit references to Nietzsche in Wittgenstein's writings and clarify their philosophical function. In Part II, the contributors take a philosophical problem as their starting point and show how it can be illuminated by comparing or contrasting Wittgensteinian and Nietzschean arguments and methods. Together the chapters trace Nietzsche's influence on Wittgenstein's thought concerning the critique of language, ethics, aesthetics, religion, and philosophical method. Wittgenstein and Nietzsche will be of interest to scholars and advanced students working in the history of philosophy and intellectual history"--